Decreasing High-risk Exposures for Healthcare Workers Through Universal Masking and Universal Severe Acute Respiratory Syndrome Coronavirus 2 Testing on Entry to a Tertiary Care Facility. (8th September 2020) - Walker, Jeremey; Fleece, Molly E; Griffin, Russell L; Leal, Sixto M; Alsip, Jorge A; Stigler, William S; Nafziger, Sarah D; Marrazzo, Jeanne M; Lee, Rachael A
Abstract: We describe the impact of universal masking and universal testing at admission on high-risk exposures to severe acute respiratory syndrome coronavirus 2 for healthcare workers. Universal masking decreased the rate of high-risk exposures per patient-day by 68%, and universal testing further decreased those exposures by 77%.